Theoretical, experimental and numerical studies on a novel laminated viscoelastomer-filled steel tube damper. (November 2022) - Zhou, Yun; Li, Jiale; Shi, Fei; He, Zhiming; Zhong, Genquan
Abstract: This study proposes a novel hybrid damper, namely, laminated viscoelastomer-filled steel tube damper (LVSTD), to improve the energy dissipation capacity and meanwhile, overcome the buckling behavior of the steel tube. A detailed introduction of the configuration, fabrication procedure, as well as working mechanism of the LVSTD was provided. Theoretical calculation formulas of the initial stiffness and yield force of the LVSTD were derived based on the principle of virtual work and the Von-Mises yield criterion. Two LVSTD specimens were designed and manufactured for experimental investigation. Cyclic loading tests were carried out to explore their mechanical behavior, low-cycle fatigue behavior, and failure mode. As a comparison, additional two hollow steel tube dampers (HSTD) were also manufactured and tested. Numerical models were established and validated in ABAQUS, followed by a numerical analysis to gain further insight into the yield state, buckling deformation, stress distribution, and equivalent plastic strain of the LVSTD and HSTD. The results reveal that LVSTD presents a stable hysteretic response with a maximum equivalent viscous damping ratio of 43.8%, indicating excellent energy dissipation capacity. Filling laminated viscoelastomer inside the steel tube is of great significance for preventing the buckling behavior of the steel tube and improving material utilization and deformability. Compared with HSTD, the LVSTD specimen exhibits higher force capacity, more stable cyclic stability, and better low-cycle fatigue performance. The weakened section of steel tube with a cambered surface in the LVSTD achieves full cross-section yielding, which is beneficial not only to improve energy dissipation capacity but also to ensure reliable end connections.